The Influence of Employees' Work Discipline Employee Work Productivity (Case Study Of Indomaret Ambon City) - Marpaung, Fransiska; Papilaya, Josef; Sinay, Francisca Riconita (JENDELA PENGETAHUAN, 2025)
This research aims to determine whether there is an influence of employee work discipline (X) on the work productivity of indomaret employees in Ambon City. This research use quantitative research with simple regression analysis techniques using the SPSS version 27 program analysis tool. This research uses primary and secondary data through observation and distribution of questionnaires. The sampling technique used purposive sampling technique, with a total of 30 respondents. The data analysis techniques used in this research are validity test, reliability test, simple regression analysis test and partial test (t test). The results of this research show that employee work discipline with indicators (x) with indicators of time discipline, regulatory discipline, responsibility and legal sanctions influences employee work productivity (Y) with indicators of work quality, work quantity, punctuality and work spirit of Indomaret employees in Ambon City. The results of determinant coefficient show that the contribution or influence of the independent variable work discipline (X) on employee work productivity at Indomaret, Ambon City is 43.6%.